Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification